Detecting changes in extreme streamflow in the Tarim River, Northwest China. (4th September 2015) - Wang, Huaijun; Chen, Yaning; Deng, Haijun; Pan, Yingping
Abstract: We analyzed the characteristics of streamflow changes in the Tarim River Basin using daily data collected at 7 hydrological stations. We ran the nonparametric Mann–Kendall test to detect trends in hydrological extremes. We also applied the Indicators of Hydrological Alteration (IHA), to assess flow regime variations. The results indicate that: (1) the hydrological extremes in headwater experienced increases in magnitude, duration, and high flow frequency; the mainstream exhibited increases in low flow duration and low flow frequency, and a decrease in high percentile flow and high flow frequency; (2) The trends of extremes related to minimum flow is greater than maximum flow; the date of maximum flow in both the headwater and mainstream has advanced; the most drastic changes in extreme streamflow occurred during winter; (3) Climate change has considerably altered flow regime in the headwater. Although climate change has profoundly affected the water supply upstream, human activities are dominant in determining flow regime.